THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND TRANSACTIONAL LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLES IN BANK "XXX" - Mashudi Mashudi; Luluk Fauziah; Tika Kapita Fachrista (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2020)
Departing from the phenomenon in the form of employee performance and job satisfaction is still low, even though transformational and transactional leadership have been running as it should be, this study aims to determine the effect of transformational leadership style and transactional leadership style on employee performance with job satisfaction as an intervening variable in the Bank "XXX ". This study uses a quantitative approach with explanatory and survey research formats. Data collection used a questionnaire to 126 respondents which were determined by simple random sampling. The data were processed using path analysis techniques assisted by the International Business Machine (IBM) Predictive Analytic Software (PASW) version 22 software. The results of this study are transformational and transactional leadership styles have a significant effect on job satisfaction and employee performance. Job satisfaction has a significant effect on employee performance. Transformational leadership style has a significant effect on employee performance through employee job satisfaction. Transactional leadership style has a significant effect on employee performance through employee job satisfaction.